Level of knowledge learning studies of the University of Medicine University in Lublin on risk factors of coronary heart disease - Krzyżanowska, Ewa; Zwolan, Ewelina; Łuczyk, Robert Jan; Kropornicka, Beata; Baczewska, Bożena; Sawicka, Katarzyna; Łuczyk, Marta; Daniluk, Jadwiga (Journal of Education, Health and Sport, 2017)
Admission. Currently, the main cause of disability, morbidity and premature death in developed countries is cardiovascular disease. This problem mainly affects Central and Eastern European countries [7,9]. Aim of the study. Assessment of the level of knowledge of the students of the Medical University of Lublin on the risk factors of ischemic heart disease. Material and method. The questionnaire survey was used by the author. 200 students from the Medical University of Lublin participated in the study. Results of the study. Most students in the Medical University (62.00%) presented the average level of knowledge about myocardial ischemia, the high level was 25.50% of the students, and the low was 12.50% of the subjects. Conclusions. Students have quite enough knowledge about the impact of stress, smoking cigarettes and drinking alcohol for cardiovascular disease. Women showed higher levels of knowledge of risk factors for coronary heart disease than men.